The exoA gene of Streptococcus pneumoniae and its product, a DNA exonuclease with apurinic endonuclease activity. - Puyet, A (1989)
The gene encoding the major DNA exonuclease of Streptococcus pneumoniae, exoA, was cloned in a streptococcal host vector system. Its location was determined by subcloning and by insertion mutations. Transfer of a DNA segment containing the gene to an Escherichia coli expression vector showed that exoA was the structural gene for the enzyme and that it was adjacent to its promoter. DNA sequence determination indicated that the gene encoded a protein, ExoA, of molecular weight 31,263. Under hyperexpression conditions, the ExoA protein constituted 10% of total cellular protein. In addition to previously demonstrated 3' to 5' exonuclease and 3'-phosphatase activities, ExoA was shown to make single-strand breaks at apurinic sites in DNA. Its enzymatic activities are thus similar to those of exonuclease III of E. coli and other gram-negative bacteria. The nucleotide sequence of exoA revealed it to be homologous to xth of E. coli, with 26% identity of amino acid residues in the predicted proteins. So far, no null chromosomal mutants of exoA have been obtained, and the biological function of ExoA remains unknown.